Association between a functional variant at PTGS2 gene 3′UTR and its mRNA expression in lymphoblastoid cell lines1. (27th February 2013) - Wang, Xueting; Zhao, Yunzhao; Wang, Yanru; Wang, Zexing; Guan, Xiaoxiang
Abstract PTGS2 genetic 3′ untranslated region (3′UTR) miRNA binding sites variants are significantly associated with cancer risk; however, the roles of genetic variants in PTGS2 gene 3′UTR and post‐transcriptional regulation have not been elucidated. We report that rs689470 and rs5275 in the PTGS2 3′UTR have potential miRNA‐binding sites by using bioinformatics analysis. However, only the rs689470 was significantly associated with PTGS2 mRNA expression in lymphoblastoid cell lines (P = 0.026), but not for rs5275 (P = 0.626). rs689470 might be putative variants mediating the post‐transcriptional regulation of target PTGS2 gene. Better understanding of how 3′UTR variants regulate PTGS2 activity will pave the way to targeting the PTGS2 pathway in cancer therapy.